Assessment of parental awareness about pediatric visual problems by Knowledge-Attitude-Practice survey in South India - Neelam Pawar; Meenakshi Ravindran; Allapitchai Fathima; K Ramakrishnan; Sabyasachi Chakrabarthy; K Aparna; Mohammed Sithiq Uduman (Indian Journal of Ophthalmology, 2023)
Purpose: To find out parents' knowledge, attitude, and treatment practice (KAP) toward pediatric eye problems and to assess the effect of demographic factors such as gender, age, educational status, and number of children on KAP. Methods: A cross-sectional descriptive study was conducted in a hospital setting. Two hundred parents were randomly selected for the questionnaire. All parents had children who were included in Systematic Pediatric Eye Care Through Sibling Screening Strategies (SPECSSS) study. A survey with 15 questions on KAP of pediatric eye diseases was prepared and administered to parents coming to a tertiary eye hospital with varied experience and education qualifications. Results: The mean age of 200 patients was 9.6 (3.4) years, with the majority of them male (n = 110; 55.0%). The majority of the children (n = 91, 45.5%) were between the age group of 6–10 years. Knowledge of visual problems among parents was of a good grade in 9% only. The attitude of the parents toward the visual problem was positive at 17%, and the responses regarding the practice were of excellent grade at 46.5% and good at 26.5%. Analysis suggests that the level of knowledge and practice were not significantly associated with the demographic factors (p > 0.05). The positive attitude toward the visual problems of the children was associated with education of the parents (p < 0.05) and the father occupation (p < 0.05). Conclusion: Knowledge about pediatric eye diseases was poor among parents and it was significantly affected by education and occupation of parents. The parents have positive attitude toward enhancing their attitude in treatment.